RETRACTION Shidiq, A. A. P., Hidayatullah, M. F.., Doewes, M.., & Ekawati,. F. F.. (2024). Eficacia del masaje tendo-muscular para la reducción del dolor y la mejora del ROM articulación de la rodilla tras una lesión (Effectiveness of Tendo-Muscular Massage for Pain Reduction and ROM Improvement Post-Injury Knee Joint). Retos, 57, 818–825. https://doi.org/10.47197/retos.v57.107501 - RETOS, RETOS (Retos, 2025)
Shidiq, A. A. P., Hidayatullah, M. F.., Doewes, M.., & Ekawati,. F. F.. (2024). Eficacia del masaje tendo-muscular para la reducción del dolor y la mejora del ROM articulación de la rodilla tras una lesión (Effectiveness of Tendo-Muscular Massage for Pain Reduction and ROM Improvement Post-Injury Knee Joint). Retos, 57, 818–825. https://doi.org/10.47197/retos.v57.107501Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that there has been a manipulation of the authorship of the article. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were necessary. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Authors in the Word document of the article submitted for review: 4Authors in the published PDF with modified authors: 4Differences between the authors between both moments: +1 y -1 (Añadido: Abdul Aziz Purnomo Shidiq. Eliminado: Hendra Setyawan)